2003
DOI: 10.1111/j.1460-2466.2003.tb03005.x
|View full text |Cite
|
Sign up to set email alerts
|

Setting the Public Fear Agenda: A Longitudinal Analysis of Network TV Crime Reporting, Public Perceptions of Crime, and FBI Crime Statistics

Abstract: Public perceptions of crime as the most important problem (MIP) facing the country jumped tenfold, from 5% in March of 1992 to an unprecedented 52% in August of 1994. This study analyzed the effects of three network television news predictor variables and two FBI predictor variables to determine what statistically accounted for this “big scare”. Based upon data from 1978 through 1998, results suggest that the 1994 “big scare” was more a network TV news scare than a scare based upon the real world of crime. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(20 citation statements)
references
References 19 publications
(18 reference statements)
1
16
0
1
Order By: Relevance
“…In addition, numerous studies have found that fear of attack is an important predictor of people carrying weapons to protect themselves 25. To date, few studies have directly examined the effect of media coverage on the uptake of weapons, but several recent US population studies have found that extensive media coverage is linked to increases in gun purchases and applications for gun licences in the aftermath of mass shootings 262728. While the evidence is at present limited to US studies, it suggests that mass publicity of violent events may prompt increases in self protective behaviours, including carrying weapons.…”
Section: Are We Fuelling the Fire?mentioning
confidence: 99%
“…In addition, numerous studies have found that fear of attack is an important predictor of people carrying weapons to protect themselves 25. To date, few studies have directly examined the effect of media coverage on the uptake of weapons, but several recent US population studies have found that extensive media coverage is linked to increases in gun purchases and applications for gun licences in the aftermath of mass shootings 262728. While the evidence is at present limited to US studies, it suggests that mass publicity of violent events may prompt increases in self protective behaviours, including carrying weapons.…”
Section: Are We Fuelling the Fire?mentioning
confidence: 99%
“…Additionally, public perceptions of crime have shown to be mostly driven by the prominence of this topic on the (television) news agenda rather than by actual crime rates (Lowry, Nio, & Leitner, 2003). Viewing the (local) news, therefore, has been shown to cause concerns about and fear of crime (Gerbner, 1988;Romer, Jamieson, & Aday, 2003).…”
Section: News Consumption and Mental Well-beingmentioning
confidence: 99%
“…For instance, research has shown that women have a greater affinity than men for victims of crime in news reports, and affinity was strongly related to fear of crime, even after adjusting for own perceived safety (Chiricos, Eschholz, & Gertz, 1997). In addition, media coverage of crime in the local area is often exaggerated and may cue people that crime can unexpectedly occur in their own homes (Lowry, Nio, & Leitner, 2003). It is possible that county-level crime rates become a key aspect of a county’s “identity” that is well known to its residents, even if they live in less-affected areas of the county.…”
Section: Discussionmentioning
confidence: 99%